Treadmill exercise activates ATF3 and ERK1/2 downstream molecules to facilitate axonal regrowth after sciatic nerve injury - Kim, Ji-Eun; Cho, Yeong-Hyun; Seo, Tae-Beom (Journal of exercise rehabilitation, 2020)
The purpose of this study was to investigate the effect of treadmill exer-cise on activating transcription factors such as activating transcription factor 3 (ATF3) and extracellular signal-regulated kinase (ERK1/2) sig-naling pathway to facilitate axonal regrowth after sciatic nerve injury (SNI). The experimental rats divided into the normal control (n=10), sedentary groups for 7 (n=10) and 14 days (n=10) post crush, exercise group for 7 (n=10) and 14 days (n=10) post crush (dpc). The rats in ex-ercise groups run on treadmill device at a speed of 8 m/min for 20 min once a day according to exercise duration. In order to evaluate specific regeneration markers and axonal elongation in injured sciatic nerve, we applied immunofluorescence staining and western blot techniques. Treadmill exercise further increased growth-associated protein (GAP-43) expression and axonal regrowth at 7 and 14 dpc than those in sed-entary group. Among mitogen-activated protein kinase downstream molecules, phospho-ERK1/2 (p-ERK1/2) was enhanced by treadmill ex-ercise at only 7 dpc and decreased to basal level 14 days later. But c-Jun N-terminal kinase, c-Jun, and phospho-cyclic adenosine mono-phosphate response element-binding protein showed a tendency to in-crease continuously until 14 dpc by exercise. ATF3 expression in exer-cise group was upregulated at both 7 and 14 dpc compared to the sed-entary group. These results indicate that treadmill exercise had benefi-cial effect on expression of regeneration-related proteins after SNI, suggesting that exercise might be one of various therapeutic strategies for sciatic nerve regeneration.